Inventarisasi Nepenthes spp. di Stasiun Penelitian Cabang Panti Taman Nasional Gunung Palung Kayong Utara - Mukarlina, Muchsin Alatas, Riza Linda (Jurnal Protobiont, 2017)
Nepenthes is a carnivorous plant wich has a unique pitcher at the tip of its leaf. This research aims to make an inventory of the kinds of Nepenthes in Cabang Panti Research Station, Gunung Palung National Park, Kayong Utara Regency. The research was conducted from October until December 2016. The sample was taken by using cruise method. The sample was observed through descriptive research, which then being recorded and identified. The results show that there were four types of Nepenthes found, namely Nepenthes ampullaria Jack, N. hirsuta Hook, N. albomarginata Lobb and N. hispida Beck.